Pemberdayaan Umat sebagai Subjek Budaya - Khuza’i, Rodliyah (Mediator, 2005)
Postmodernism has penetrated human thinking in everywhere. As consequences, postmodernism affected interreligious relationship, intercultural connection, and civilization as well. There are at least three characters of postmodernism: deconstruction, pluralism, and relativism. This characters are functioned as methodology to comprehend religious in terms of postmodernism canons. By understanding religion using this methodology, religion is playing a role as filter of negative effect resulted from modernity and postmodern process. Religion also could be actively utilized to strengthen nation culture and religious life.